Indigenous Research: Three Researchers Reflect on their Experiences at the Interface - Minniecon, Deanne; Franks, Naomi; Heffernan, Maree (The Australian Journal of Indigenous Education, 2007)
Abstract Utilising Nakata’s (2007) description of the “cultural interface”, two Indigenous researchers and one non-Indigenous researcher examine their development of Indigenous research in and with Aboriginal and Torres Strait Islander communities conducted from within an institution of higher education. The authors reflect on their experiences in developing an Indigenous research project and use Indigenous standpoint theory as a device to explore these experiences. The framing of priorities and research questions, ethics processes, the treatment of project information or data, the managing of competing accountabilities, and the role of non-Indigenous researchers in Indigenous research are all explored in these reflections.